ANALISIS KESIAPAN GURU SEKOLAH DASAR DALAM MENGHADAPI TRANSISI DARI KURIKULUM 2013 KE KURIKULUM MERDEKA - Sofyan Iskandar; Anggita Okthaviani; Afrilia; Aulia Nurfazriah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The transition to the Merdeka Curriculum requires teachers in primary schools to change their way of thinking and teaching techniques. This curriculum focuses on learning that is tailored to student needs, project-based, and reinforces the values of the Pancasila Student Profile, which requires high skills and independence from teachers. Through descriptive quantitative analysis with questionnaires, it was found that in terms of cognitive, 80% of teachers were in the highly prepared category, 11.11% slightly prepared, and 8.89% less prepared. Meanwhile, in terms of practical and professional aspects, 73.33% of teachers were very prepared, 6.67% were slightly prepared, and 20% were less prepared. This finding shows that the majority of teachers have understood the direction of the curriculum change and are willing to implement it at school. However, there are still challenges such as the lack of training, inadequate facilities and an incomplete understanding of the curriculum structure. These results emphasize the importance of teacher readiness and the need for support through training and continuous professional development to ensure the successful implementation of Merdeka Curriculum.